Badut Jalanan: Transformasi Hiburan Menuju Belas Kasihan - Zakia Safitri Sijaya; Hilda Amalia Kaharuddin; Wijangga, Putu; Achamadinar, Pradiva Mulya; Rahmayani, Siti Nur (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2024)
Street clowning is another practice of begging and is still relatively new in the city of Makassar with 1.427 million inhabitants. Poverty and inequality are the main reasons for the presence of this new profession. This is also inseparable from the impact caused by the COVID-19 pandemic. With that, this research aims to analyze the factors that cause the emergence of street clowns in Makassar City and how community participation sees this problem. This research uses a qualitative method with a case study approach and a purposive sampling technique.  The data in this research was obtained through interviews, field observations, and literature studies which were then analyzed using fishbone analysis. The results of this research show that four factors caused the emergence of street clowns in Makassar City: economic factors, education and work environment, environment, and family. In addition, the forms of community participation in this problem are participation for material intensive, participation with consultation, participation with resource contribution, and participation in the form of programs.